Rancang Bangun Sistem Monitoring Tanaman Lidah Buaya Menggunakan ESP32 Berbasis IoT - Muzakkir, Taufik; Ilyas, Mohd; Radwitya, Erick; Hartanto, Hartanto; Hasan, Hasan; Yuwono Tharam , Medi (Electrical Network Systems and Sources, 2024)
Aloe vera grows at temperatures between 16-33°C. Growth is also strongly influenced by humidity. If the humidity of the environment is outside the limit, then the plant will be disrupted growth. For aloe vera plants, which are needed around 80%, the ideal soil humidity is 40%-60% and the ideal pH level for aloe vera plants is 4.5 - 7.0 optimum pH 5.5. The aloe vera plant monitoring system uses a DHT22 sensor, soil pH sensor, and Soil Moisture sensor connected to an ESP32 microcontroller. These sensors read temperature, air humidity, soil moisture, and soil pH. Based on the read values, the system regulates the fan, spotlight, and pH neutralizing pump as well as watering the soil automatically. The fan is turned on when the temperature exceeds 32 degrees Celsius, the floodlight when the air humidity exceeds 80%, and the pH pump activates when the soil pH is less than 4.5, the water pump also waters the soil when the soil moisture is less than 40%. Sensor data is displayed through the Blynk application and LCD making it easier to monitor aloe vera plants.